2019
DOI: 10.1371/journal.pone.0218953
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction between somatostatin analogues and targeted therapies in neuroendocrine tumor cells

Abstract: Somatostatin analogues (SSA) represent the standard of care for symptom control in patients with functional gastro-entero-pancreatic neuroendocrine tumors (GEP-NET). In addition, SSA exert significant anti-proliferative effects in mid-gut and pancreatic NET (PanNET). In parallel, molecularly targeted therapies (MTT) have been shown to improve progression free survival (PFS) in patients with PanNET. However, due to either primary or acquired resistance to MTT, their impact on overall survival (OS) remains uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
1
2
0
1
Order By: Relevance
“…Vitale and colleagues showed a synergy between everolimus and demethylating agent 5-aza-2 0 -deoxycytidine (AZA) in chemoradiotherapy resistant medullary thyroid cancer cells (23). We did not observe any synergy with everolimus and somatostatin analogs which is in agreement with the findings of Krug and colleagues (24), however, a study has demonstrated that lanreotide inhibited the cell growth syngergistically in everolimus-resistant BON1 cells (25). In contrast, Hue-Fontaine and colleagues did not observed synergy between everolimus and metformin in the diabetic patients (26) maybe because of the targeting of same pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Vitale and colleagues showed a synergy between everolimus and demethylating agent 5-aza-2 0 -deoxycytidine (AZA) in chemoradiotherapy resistant medullary thyroid cancer cells (23). We did not observe any synergy with everolimus and somatostatin analogs which is in agreement with the findings of Krug and colleagues (24), however, a study has demonstrated that lanreotide inhibited the cell growth syngergistically in everolimus-resistant BON1 cells (25). In contrast, Hue-Fontaine and colleagues did not observed synergy between everolimus and metformin in the diabetic patients (26) maybe because of the targeting of same pathway.…”
Section: Discussionsupporting
confidence: 91%
“…SSTR2 are not only expressed by neuroendocrine neoplastic cells, but also by some tumor-infiltrating B-cells. Hence, direct anti-proliferative effects of octreotide on both neoplastic and immune cells of the tumor microenvironment are possible [ 34 ]. On the other hand, it is tempting to speculate that, by targeting neoplastic lymphocytes, PRRT may have coincidently improved the immunocompetence status of our CLL patients, as the peripheral lymphocyte counts of both patients substantially decreased during treatment, and neither patient showed CLL exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Expression of somatostatin receptors 2 and 5 is common in NETs, and these receptors modulate hormone and growth-factor release, angiogenesis, and other functions. 19 SSAs are first-line therapy for well-differentiated G1 or G2 tumors with somatostatin receptor expression and are approved as treatment for the hormonal-induced syndromes, including carcinoid syndrome, associated with functional NETs. The PROMID and CLARINET studies demonstrated the antiproliferative effects of SSAs in patients with well-differentiated NETs.…”
Section: Current Therapiesmentioning
confidence: 99%